Advanced nutrition : macronutrients, micronutrients, and metabolism. - Berdanier, Carolyn D., ....-; Zempleni, Janos, ....- (Boca Raton : CRC, 2009)
Integrating nutrition science with biochemistry, genetics, and physiology, this textpresents key concepts in nutrition science, with emphasis on the role of macro- and micronutrients in energy metabolism. Revising and expanding information from "Advanced Nutrition Micronutrients and Advanced Nutrition Macronutrients, Second Edition," this renovated work includes new chapters on the regulation of food intake, daily recommendations, nutrition assessment, metabolism, toxicology, nutrigenomics, epigenetics, gene expression, cell cycle, and lifespan nutrition. It includes a glossary, clinical correlates, diagrams, supplemental readings, and a CD-ROM with laboratory exercises and PowerPoint illustrations.
Keywords: Voeding